OPTIMALISASI PERALATAN PENGOLAHAN MINERAL DI KAMPUS LAPANGAN CIPATAT PADALARANG - Imelda Hutabarat; Revi Timora Salajar (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2018)
A good quality of training requires a well-prepared equipment, infrastructure, and facilities, including the Indonesian National Working Competency Standards (RSKKNI), Curriculum Standards, and Modules and Competency Testing Material (MUK). The purpose of this paper is to design the flowing process by preparing the equipment, infrastucture, and facilities of the Mineral Processing field in PPSDM Geominerba Campus Cipatat Padalarang to be utilized optimally for the tainings held by PPSDM Geominerba. The design preparation begins with a literature study of the raw material types for the mineral processing process by considering its availability, mineral types, the processing plan, and the necessary equipment. Furthermore, the arrangement of the flowing process for non-metallic minerals (limestone) and metallic minerals (gold) is done which then can set the position of the equipment in the Mineral Processing field of Campus Cipatat Padalarang, West Java. Through this paper, the optimization of mineral processing equipment in Campus Cipatat Padalarang can be realized, especially for Non-Metal Minerals Processing Training (limestone) and Metal Minerals Processing Training (gold). Limestone can be processed to obtaine a fine concentrates which is ready for the combustion process to produce a fine limestone which meets the subsequent industries. Meanwhile, the metal minerals (gold) can be processed through the comminution process with jaw crusher and ball mill. The process can be done with the shaking table to produce a gold concentration which is ready for the gold smelting.